DIGITAL MARKETING STRATEGIES TO IMPROVE MARKETING EFFECTIVENESS AND SALES PERFORMANCE OF MSMEs IN THE FOOD SECTOR - Tabroni, Tabroni; Bahits, Abdul; Suflani, Suflani; Salapudin, Salapudin; Wulansari, Retno (Yayasan Education and Social Center, 2025)
This research aims to analyze how digital marketing strategies can improve marketing effectiveness and sales performance of MSMEs in the food sector in Indonesia. Using a qualitative approach, simulation data was collected through semi-structured interviews with 12 MSME actors in the food sector (traditional food traders, small cafes, and packaged food businesses) as well as observing their social media content. Thematic analysis revealed that social media, especially Instagram and TikTok, are effective in increasing brand visibility and customer engagement, with visual content and local influencer collaborations as key factors. However, low digital literacy and budget constraints are significant obstacles. Opportunities such as digital training programs from the government and increased internet access in rural areas support digital marketing adoption. This research integrates the AIDA Model and Theory of Planned Behavior to understand the adoption behavior of MSME actors, as well Diffusion of Innovation to analyze the spread of digital innovation. The research results offer a theoretical framework for academics and practical guidance for MSME actors and policy makers to strengthen the digitalization of MSMEs in the food sector. Policy implications include increasing digital literacy training and technology subsidies to support the competitiveness of MSMEs.